Testing mental health awareness communication materials targeting first responders: an exploratory study - ODare, Kellie; Atwell, Leah; Porter, Lauren; Carlson-Moore, Brandy (Frontiers in Communication, 2026)
IntroductionFirst responders may face significant challenges impacting their mental well-being, yet mental health services are historically underutilized due to barriers such as stigma, fear of consequences, and lack of occupationally competent programs. Effective communication strategies are essential to encourage help-seeking behavior among this group.ObjectiveThis research aimed to test campaign materials designed to motivate first responders to utilize mental health resources and gather data to inform the development of effective behavior change campaigns. Method: Using a cross-sectional survey, researchers assessed first responders’ attitudes toward various mental health campaign materials. The survey included mental health advertisements and Likert-scale statements, allowing participants to prioritize advertising methods and rate their preferences for commonly used terminology.ResultsOut of 245 respondents, 149 completed at least 75% of the survey and were included in the analysis. The results showed that billboards were least effective in influencing information-seeking, while social media posts with real images and testimonials of first responders ranked highest. Respondents emphasized the importance of credibility, trust, and the use of real images in effective messaging. Social media and in-person visits were identified as the most effective ways to reach first responders. Terminology focused on resiliency and mental wellness was preferred over terms like “hero” and “warrior.”DiscussionPromoting mental health among first responders requires targeted communication strategies that resonate with their experiences. Strengths-based imagery and messaging, along with consistent mental wellness programs, are recommended to support first responders’ mental health. Leadership within their organizations plays a crucial role in reinforcing these messages.